Ladybird tales rapunzel (Ladybird UK, 2006)
Ladybird Readers is an ELT graded reader series for children aged 3--11 learning English as a foreign or second language. The series includes traditional tales, popular characters, modern stories, and non-fiction. - Beautifully illustrated books, carefully written by language learning experts. - Structured language progression to develop children's reading, writing, speaking, listening and critical thinking skills. - Eight levels follow the Common European Framework of Reference for language learning (CEFR). - Language activities provide preparation for the Cambridge English Pre-A1 to A2 (YLE) tests. - A unique code in each printed book provides access to online audio, extra activities and learning resources.Rapunzel, a Level 3 Reader, is A1+ in the CEFR framework and includes practice for the Cambridge English A1 Movers tests. The longer text is made up of sentences with up to three clauses, some expression of future meaning, comparisons, contractions and relative clauses.Taken from her parents by a witch, poor Rapunzel lives alone in a tower. Until, one day, a prince rides by . . .Visit the Ladybird Education website for more information.